2020
DOI: 10.21203/rs.3.rs-23683/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mechanisms underlying the predictive power of high skeletal muscle uptake of FDG in Amyotrophic Lateral Sclerosis

Abstract: BackgroundUsing a computational approach to PET/CT images, we recently reported that enhanced 18F-fluorodeoxyglucose (FDG) uptake in skeletal muscles predicts aggressiveness and outcome in patients with amyotrophic lateral sclerosis (ALS). The present experimental study aimed to assess the mechanisms underlying the predictive potential of this metabolic shift in SOD1G93A mice as a model of ALS.Methods.The study included 15 SOD1G93A mice and 15 wild-type mice (around 120-days-old). Mice were submitted to micro-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…The effects of ALS on metabolic function in humans and in animal models of ALS are yet to be fully understood. In animals, only one study has measured the impact of SOD1 G93A genotype on glucose uptake using [ 18 F]-FDG, however focus was specifically placed onto metabolic changes in skeletal muscles (7). Marini et al found that mice expressing mutant SOD1 G93A had a higher [ 18 F]-FDG uptake in quadriceps when compared with WT animals, indicative of a higher metabolic rate.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of ALS on metabolic function in humans and in animal models of ALS are yet to be fully understood. In animals, only one study has measured the impact of SOD1 G93A genotype on glucose uptake using [ 18 F]-FDG, however focus was specifically placed onto metabolic changes in skeletal muscles (7). Marini et al found that mice expressing mutant SOD1 G93A had a higher [ 18 F]-FDG uptake in quadriceps when compared with WT animals, indicative of a higher metabolic rate.…”
mentioning
confidence: 99%
“…Marini et al found that mice expressing mutant SOD1 G93A had a higher [ 18 F]-FDG uptake in quadriceps when compared with WT animals, indicative of a higher metabolic rate. These changes were accompanied by increased inflammatory profiles and mitochondrial dysfunction in muscle (7). In humans, however, the assessment of brain metabolism in ALS patients with [ 18 F]-FDG PET has been studied with a focus on prediction of ALS onset and characterization of disease progression, both with mixed results (5).…”
mentioning
confidence: 99%